Multichannel Ordered Contention MAC Protocol For Underwater Wireless Sensor Networks. (20th August 2020) - Roy, Alak; Sarma, Nityananda
Abstract: Recent advancement in hardware and the availability of bandwidth open scope for multichannel communication in underwater wireless sensor networks. Utilizing multiple channels for data and control packets in bursty traffic networks can reduce collisions due to several contending nodes. The paper presents a synchronous reservation-based multichannel ordered contention MAC protocol for deep underwater high data rate bottom monitoring applications to improve the overall network throughput. This protocol is proposed as an enhancement over ordered contention MAC (OCMAC) protocol to deal with bursty traffic by reducing transmission collisions. It does so by enabling nodes to employ multichannel technique along with the scheduling technique of OCMAC. The protocol uses separate channels for channel reservation and data transmission. The throughput performance of the network has been analyzed and validated through simulation. Simulation-based results have shown that MOC-MAC outperforms OCMAC in terms of throughput.